The effects of growth rate and biomechanical loading on bone laminarity within the emu skeleton - Kuehn,Amanda L.; Lee,Andrew H.; Main,Russell P.; Simons,Erin L.R. (PeerJ, 2019)
The orientation of vascular canals in primary bone may reflect differences in growth rate and/or adaptation to biomechanical loads. Previous studies link specific canal orientations to bone growth rates, but results between different taxa are contradictory. Circumferential vascular canals (forming laminar bone) have been hypothesized to reflect either (or both) rapid growth rate or locomotion-induced torsional loading. Previous work on the hindlimb biomechanics in the emu shows that the femur and tibiotarsus experience large shear strains, likely resulting from torsional loads that increase through ontogeny. Here, we test how growth rate and biomechanical loading affect bone laminarity in wing and hindlimb elements from growing emu (2–60 wks). If laminar bone is an adaptation to torsion-induced shear strains, it should increase from juveniles to adults. Alternatively, if bone laminarity reflects rapid growth, as has been shown previously in emu, it should be abundant in fast-growing juveniles and decrease with age. Transverse mid-shaft histological sections from the limb bones (femur, tibiotarsus, humerus, ulna, and radius) were prepared and imaged. Growth rates were measured using fluorescent bone labels. Vascular canal orientation was quantified using laminarity index (proportion of circumferential canals). Principal components analysis was performed to convert highly correlated variables (i.e., mass, age, growth rate, and shear strain) into principal components. Random-intercept beta regression modeling determined which principal components best explained laminarity. The fastest growth rates were found in young individuals for all five skeletal elements. Maximum growth rate did not coincide with peak laminarity. Instead, in the femur and tibiotarsus, elevated laminarity is strongly correlated with adult features such as large size, old age, and modest growth rate. This result is contrary to predictions made based on a previous study of emu but is consistent with results observed in some other avian species (penguin, chicken). Shear strain in the caudal octant of the femur and tibiotarsus is positively correlated with laminarity but has a weaker effect on laminarity relative to mass, age, and growth rate. Laminarity in the wing elements is variable and does not correlate with ontogenetic factors (including mass, age, and growth rate). Its presence may relate to relaxed developmental canalization or a retained ancestral feature. In conclusion, ontogeny (including growth rate) is the dominant influence on vascular canal orientation at least in the hindlimb of the emu.
Keywords: Laminarity; Growth rate; Torsion; Shear strain; Bone; Emu